Using surface water resource under salinity intrusion from inclusive innovation perspective in An Bien district, Kien Giang province - Nguyen Thanh Binh; Le Van Thuy Tien; Nguyen Hieu Trung; Nguyen Thi Ngoc Bau; Bach Tan Sinh; Nguyen Nguyen Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
Research on the change of surface water resource use in the condition of salinity intrusion from the perspective of inclusive innovation was carried out in An Bien district of Kien Giang province. The results show that people have had the initiative to switch from a rice monoculture model to a shrimp-rice combination model to adapt to saline intrusion and climate change. This transition took place quickly after the historic drought in 2015-2016 and was created by the local government with a legal framework to allow the transition from 2017. The shrimp-rice model was evaluated by farmers as an appropriate model in terms of natural conditions, high economic efficiency, less environmental pollution compared to rice monoculture. Agro-products are diverse and ecological. The lesson learned from this study is that in order to promote inclusive innovation, active and timely stakeholder engagement is important. Code: 21120101